Broad-Based Student Learning Outcomes: An Assumed Assessment Reality Check Experience In Aviation - Barnard, Kenneth W. (My University, 2010)
Broad based Student Learning Outcomes (SLO) are being used and are becoming commonplace as accreditation requirement processes. Assessment of these SLO’s are then required to ensure the SLO’s are being met by the education entity. The problem then becomes one of identifying valid assessment tools. When assumptions are made in education knowledge levels or even skill performance, assessment error can occur. In aviation we have specific knowledge and skill performance levels set by Federal Regulations. One of our assumptions was students that met or exceeded these established and measurable standards were then ready to met our SLO’s. One such SLO states for example that: “Students will be highly skilled professional aviators who understand the national airspace system and can interface with all facets of the air traffic control system”. To our surprise our students did not meet this SLO. This shortcoming came to our attention when we put our students in the right seat (serving Co-Pilot duties) of our C90 and C525 university transportation aircraft. The transportation Captain’s feedback related that the operational and performance level of the students was very low and did not meet basic standard expectations. To address this training short fall, PPIL 416 Crew Resource Management course was designed using a Flight Training Device similar to the C525 jet where Line Orientation Flight Training scenarios were flown. The student knowledge and skill level was improved dramatically to the point that we do meet the SLO. Direct feedback from the employer or in this case a quasi employer where the student is actually performing the mission their education and training is designed for is a necessary element for validating broadly stated Student Learning Outcome’s. This lesson should be applicable across disciplines.
Keywords: Aviation education; Assessment; Student learning outcomes